2012
DOI: 10.3329/bjnut.v22i0.12833
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Homocysteine, Folate and Vitamin B<sub>12</sub> in Different Trimester of Pregnancy

Abstract: Abstract:The present study has been undertaken to investigate plasma creatinine, folate and vitamin B 12 as underlying factors in the reduction of plasma homocysteine concentration in different trimesters of pregnancy. Under a cross-sectional design, 30 healthy nonpregnant as well as 130 pregnant women, at 3 different trimesters of pregnancy (43 in 1 st trimester, 44 in 2 nd trimester and 43 in 3 rd trimester) were sampled for plasma levels of folate, vitamin B 12, homocysteine and creatinine. Plasma homocyste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Although both plasma folate and tHcy levels are significantly different in pregnant women than non-pregnancy women [48], no statistical significances were observed between first trimester and second trimester with plasma folate and tHcy levels. No previous study has investigated the relationship between plasma folate levels tendency and gestational weeks.…”
Section: Discussionmentioning
confidence: 76%
“…Although both plasma folate and tHcy levels are significantly different in pregnant women than non-pregnancy women [48], no statistical significances were observed between first trimester and second trimester with plasma folate and tHcy levels. No previous study has investigated the relationship between plasma folate levels tendency and gestational weeks.…”
Section: Discussionmentioning
confidence: 76%
“…Folate also plays an important role in two biochemical cycles, which are biosynthesis DNA and carbon metabolism such as DNA, lipid, and protein methylation. 24,25 The average Hcy levels in subjects with macrocytic anemia (case group) were10,2±5,5 µmol/L. Meanwhile, the average Hcy levels in subjects without anemia (control group) was 12,9±8,2 µmol/L.…”
Section: Resultsmentioning
confidence: 96%
“…Folate also plays an important part in two biochemical cycles, which are DNA biosynthesis and carbon metabolisms such as DNA, lipid, and protein methylation. 24,25 Up until now, several researchers had studied how Hcy levels can affect HIV patients, but the results were controversial. Look et al found hyperhomocysteinemia (HHcy) in 35% of HIV patients who received HAART.…”
Section: Introductionmentioning
confidence: 99%